Qualitative research in organizations and management. - Lee, Bill; Collier, Paul M.; Cullen, John (Journal of management history, 2007)
This ebook is a review of developments in both the qualitative tradition and case studies in management research. The articles discuss: the merits of unique cases and singular forms of evidence within a single case; the comparability of case studies with tools in other areas; and methods of theorizing from case studies. Readers may read each of the subsequent papers in this ebook, either as individual contributions that have merits per se, or as part of a collection. The merits of case studies have often been understated. The articles in this ebook highlight a broader variety of uses of case s.